Effect of six weeks resistance training on nerve conduction velocity, strength, balance and walking speed in Multiple Sclerosis patients - Rasoul Eslami; Bakhtyar Tartibian; Mojtaba Najarpour (مجله دانشگاه علوم پزشکی گرگان, 2019)
Background and Objective: Multiple sclerosis (MS) is the most common disabling neurological disease which leads to nerve conduction velocity (NCV) reduction and finally reduction of functional abilities. This study was executed to determine the effect of six weeks resistance training on NCV, strength, balance and walking speed in Multiple Sclerosis patients. Methods: In this quasi-experimental study, 23 MS patients were nonrandomly divided to control (n=10) and resistance training (n=13) groups. Two days before and after training program, NCV, strength, balance and 25 foot walking tests was executed. Resistance training protocol was included tree sessions per week for six weeks and intensity of training was 55% of 1RM. Results: Six weeks of lower body resistance training significantly increased nerve conduction velocity (NCV) (P<0.05), strength (P<0.05), balance (P<0.05) and walking speed (P<0.05) in MS patients. Conclusion: Controlled resistance training can improve Multiple Sclerosis patient’s nerve conduction velocity which finally can lead to improve functional abilities, such as strength, balance and walking speed.